Analisis Pola Identifikasi Zero Knowledge Proof Dengan Algoritma Feige Fiat Shamir Menggunakan Blum Blum Shub - Panjaitan, Cherlina Helena Purnamasari; Pangaribuan, Lisda Juliana (LPPM UNIKA Santo Thomas Medan, 2021)
Protocol Zero Knowledge Proof is one of the protocols in Cryptography that has a fairly good level of security, because it applies the concept of